Media Flipbook Digital Berbasis Kearifan Lokal untuk Meningkatkan Hasil Belajar IPAS Siswa Kelas V SD - Yohana Dilafatul Hamidah; Karimatus Saidah; Wahid Ibnu Zaman (YASIN, 2026)
Students’ low understanding of historical relics and the limited connection between the material and the surrounding cultural environment indicate the need for learning media that are contextual, engaging, and relevant to elementary school students’ learning experiences. This study aims to develop a Digital Flipbook based on Kediri local wisdom and to test its validity, practicality, and effectiveness in improving students’ learning outcomes on historical relics material in fifth-grade elementary school. This study used a Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 37 fifth-grade students at SDN Sukorame 2 Kediri City, including 10 students in the limited trial and 27 students in the broad trial. Data were collected through expert validation sheets, teacher and student response questionnaires, and learning outcome tests through pretest and posttest. The results of the study show that the Digital Flipbook based on Kediri local wisdom obtained a validity level of 94% in the highly valid category. The practicality of the media was shown by teacher responses of 94% and student responses of 93%, both of which were in the highly practical category. The students’ mean score increased from 64.81 in the pretest to 91.85 in the posttest. The results of the Wilcoxon Signed Rank Test showed a significance value of 0.001 (p < 0.05), indicating a significant improvement in learning outcomes after the use of the media. The conclusion of the study affirms that the Digital Flipbook based on Kediri local wisdom is valid, practical, and effective in improving students’ learning outcomes on historical relics material in fifth-grade elementary school. The implications of this study indicate that digital learning media based on local wisdom can serve as an alternative form of contextual learning that supports improved learning outcomes while introducing and preserving regional cultural heritage among students.